FREQUENCY ANALYSIS OF AN ARM OF MACPHERSON SUSPENSION ON A PASSENGER CAR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The smoothness, ride comfort, safety and handling of the car depends on the manner of suspension design and its corresponding details. One of main functions of the arm and the rubber bushings mounted on it is to reduce the vibrations and the noise transferred from the road to the passenger car components. This article presents the results of a frequency analysis of an arm of the MacPherson front independent suspension. For this purpose, three-dimensional geometric models of the arm and rubber bushings are created via finite element analysis (FEA) software SolidWorks, where Skoda Octavia passenger car was used as a prototype. The axial, radial and torsional stiffness of the rubber bushings were determined through analytical dependences and FEА. The obtained results had been used for calculation of the natural frequencies and mode shapes of the arm which were compared with experimentally obtained data.